Reported and intended behaviour towards those with mental health problems in the Czech Republic and England - Winkler, P; Csémy, L; Janoušková, M; Mladá, K; Bankovská Motlová, L; Evans-Lacko, S (European psychiatry, 2015)
This is one of the first studies, which compares the level of stigmatizing behaviour in countries that used to be on the opposite sides of the Iron Curtain. The aim was to identify the prevalence of reported and intended stigmatizing behaviour towards those with mental health problems in the Czech Republic and to compare these findings with the findings from England. The 8-item Reported and Intended Behaviour Scale (RIBS) was used to assess stigmatising behaviour among a representative sample of the Czech population (n=1797). Results were compared with the findings of an analogous survey from England (n=1720), which also used the RIBS. The extent of reported behaviour (i.e., past and present experiences with those with mental health problems) was lower in the Czech Republic than in England. While 12.7% of Czechs reported that they lived, 12.9% that they worked, and 15.3% that they were acquainted with someone who had mental health problems, the respective numbers for England were 18.5%, 26.3% and 32.5% (P<0.001 in each of these items). On the other hand, the extent of intended stigmatizing behaviour towards those with mental health problems is considerably higher in the Czech Republic. Out of maximum 20 points attached to possible responses to the RIBS items 5-8, Czechs had a lower total score (x=11.0, SD=4.0) compared to English respondents (x=16.1, SD=3.6), indicating lower willingness to accept a person with mental health problems (P<0.001). The prevalence of stigmatizing behaviour in the Czech Republic is worrying. Both, further research and evidence based anti-stigma interventions, should be pursued in order to better understand and decrease stigmatizing behaviour in the Czech Republic and possibly across the post-communist countries in Central and Eastern Europe.
Keywords: Anglie; Male; socioekonomické faktory; lidé středního věku; Socioeconomic Factors; Ethnopsychology; Social distance; Mental illness; společenské stigma; etnopsychologie; Behavioral Research; Humans; Middle Aged; senioři; Czech Republic; Česká republika; mužské pohlaví; Female; mladiství; Post-communism; duševní zdraví; Central and Eastern Europe; Aged; Stigma; ženské pohlaví; Mental Health; Mental Disorders; Adult; Stereotyping; England; stereotypizace; Adolescent; duševní poruchy; Social Stigma; dospělí; lidé; behaviorální výzkum